Selection of gasifier for the generation of electrical energy at small scale using agricultural biomass (Nexo Revista Científica, 2021)
In this article, different types of gasification equipment for the conversion of biomass from agricultural residues into electrical energy on a small scale are analyze. The Grounded theory was used through a methodological process that included the analysis of citations, codes, memos, code families and the relationships between these elements through the examination of networks to study the different types of gasifiers and link the concepts that allowed their selection for a specific application. In addition, the qualitative comparison method was used with technical indicators and criteria to determine that the moving bed gasifier (down draft) is more appropriate for the generation of electricity from the gasification of biomass from agricultural residues on a small scale.